2007
DOI: 10.1109/acc.2007.4282479
|View full text |Cite
|
Sign up to set email alerts
|

Micro UAV Path Planning for Reconnaissance in Wind

Abstract: The problem addressed in this paper is the control of a Micro Unmanned Aerial Vehicle (MAV) for the purpose of obtaining video footage of a set of known ground targets with preferred azimuthal viewing angles, using fixed onboard cameras. Control is exercised only through the selection of waypoints, without modification of the MAV's pre-existing autopilot and waypoint following capability. Specifically, we investigate problems and potential solutions of performing this task in the presence of a known constant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 10 publications
1
43
0
1
Order By: Relevance
“…The study includes the most comprehensive set of requirements including the ones overlooked in a wide range of studies. This study extends existing literature 1,3,20,21,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] by placing a special importance on aviation rules and utilisation considerations. The model generates suitable paths that address UAV performance limitations, environmental factors, basic aviation rules, flight dynamics, UAV utilisation considerations and user requirements.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The study includes the most comprehensive set of requirements including the ones overlooked in a wide range of studies. This study extends existing literature 1,3,20,21,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] by placing a special importance on aviation rules and utilisation considerations. The model generates suitable paths that address UAV performance limitations, environmental factors, basic aviation rules, flight dynamics, UAV utilisation considerations and user requirements.…”
Section: Introductionsupporting
confidence: 60%
“…A complex dynamic environment is the one that includes many constraints with different characteristics and various mission, flight, and environment related requirements. Even though, studies in autonomous path planning 1,3,20,21,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] address many challenges, domainspecific operational issues, such as utilisation considerations and aviation rules, did not receive adequate attention. This is important if the UAV under study is a medium altitude high endurance (MALE) UAV, because these types of UAVs are subject to aviation rules in addition to other criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Vector field guidance has demonstrated robustness to wind disturbance by utilising ground speed and course for navigation [7]. It was shown that path planning with a known constant wind can improve mission accuracy and efficiency [8]. By using pre-computed information of aircraft turning performance in wind, it has also been shown that path following in wind can be improved [9].…”
Section: Introductionmentioning
confidence: 98%
“…From (16) shows that ν k = ω 0ŝk drives particle k in a fixed circle of radius |ω 0 | −1 . Consider the change of variablesγ k =γ k − Ωt, which impliesγ…”
Section: Iiic Time-splay Formation With a Rotating Flowfieldmentioning
confidence: 99%
“…Some existing algorithms support operations in spatially uniform flowfields. 16,17 However, the authors are not aware of any existing theoretically justified motion-coordination algorithms for spatially and temporally varying flowfields. This problem is partially addressed here by providing decentralized control algorithms for motion coordination in a moderate, timevarying flowfield (i.e., between 10% and 99% of platform speed).…”
Section: Introductionmentioning
confidence: 99%